Implementation of feature selection and weighting methods for emotion recognition from human actions - Nurnadia Mohamad Khair (School of Mechatronic Engineering, 2016)
This thesis presents a systematic approach to investigate emotion in human actions. The research work concentrates on the implementation of the feature enhancement techniques for improving the recognition rate of emotion in human actions. Biological motion library database was used in this study. Four different emotions namely angry, happy, neutral and sad and four actions namely knocking, throwing, lifting and walking were considered.